Is There a Need for the Re(dis)covery of Teaching? - Gert Biesta (New Zealand Journal of Teachers' Work)
Earlier this year I published a book with the title The Rediscovery of Teaching (Biesta 2017). In the book I make the case that teaching matters. But unlike a significant part of contemporary discourse, I argue against the idea that the reason why teaching matters is that it has the capacity for driving test scores in the narrow set of curricular subjects that the Global Education Measurement Industry is keen to measure, not just to identify ‘quality,’ but also to ‘name and shame’ countries that are apparently not performing ‘well’ – a naming and shaming where, unfortunately, teachers often find themselves at the receiving end.